The line and the circle. Richard Flanagan and «the strange, terrible neverendingness of human beings» (ENTHYMEMA, 2021)
The paper concerns the representation of the Second World War in twenty-first-century fiction. By using Richard Flanagan’s The Narrow Road to the Deep North as a case study, I show how contemporary fiction about the war avoids both the postmemorial paradigm that characterized the late twentieth-century, and postmodern historiographic metafiction. By recovering and renewing the traditional tropes of the nineteenth-century novel, together with eclectic references to Zen art forms (haiku and ensō), The Narrow Road to the Deep North offers an anti-rhetoric and anti-nationalistic approach to the historical fiction about the Second World War. Far from being a merely ornamental addition, the references to Zen Buddhism complicate the issues discussed in the novel, from the memory of the war in Australia and Japan to colonial power structures, offering an idea of history as knowable, but also as dynamic and plastic.
Keywords: Post-Postmodernism; Contemporary fiction; Second World War; Richard Flanagan; Buddhism